Jawabanmu

Jawaban paling cerdas!
2014-03-08T18:46:42+07:00
Jika f(x) = 2x^2- x
maka f(x+1)
           = 2x^2-x+1

sorry kalau salah
              


1 5 1
2014-03-08T18:47:26+07:00
F(x)=2x kuadrat - x
f(x+1)=2 (x+1)kuadrat - x+1
         =2 (x kuadrat+2x+1) -x+1
           =2xkuadrat+ 4x + 2 -x+1
             =2x kuadrat- 3x +3
f(x)= 2x^2-x
maksudnya?
f(x) = 2x^2 - x
f(x+1) = 2 ( x + 1 )^2 - ( x + 1 )
= 2 ( x^2 + 2x + 1 ) - ( x + 1 )
= 2x^2 + 3x + 1
eh iya maaf kurang teliti haruse + aq tulis - :D muup ya
f(x)=2x kuadrat - x
f(x+1)=2 (x+1)kuadrat - x+1
=2 (x kuadrat+2x+1) -x+1
=2xkuadrat+ 4x + 2 -x+1
=2x kuadrat-+3x +

salah lg kah?